2020
DOI: 10.1590/1980-5918.033.ao53
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and postoperative complications in oncologic surgeries

Abstract: Introduction: Oncological patients who are submitted to surgical procedures might have postoperative pulmonary complications (PPCs). Thus, preoperative physical conditions must be considered, since it is an important predictor of postoperative development. Objective: The purpose of this study was to analyze the risk factors for postoperative pulmonary complications that might compromise the recovery after oncologic surgery. Method: The present observational transversal study was made between March and Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
3
0
3
Order By: Relevance
“…As noted earlier, understanding the effect of P-IMT on inspiratory muscles is important because of the negative correlation previously observed between MIP and PPCs. 40 With similar intensity and frequency, the short-term effect of P-IMT on MIP was contradictory. Two studies reported a significant short-term reduction in postoperative MIP prior to recovering to the preoperative state without significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, understanding the effect of P-IMT on inspiratory muscles is important because of the negative correlation previously observed between MIP and PPCs. 40 With similar intensity and frequency, the short-term effect of P-IMT on MIP was contradictory. Two studies reported a significant short-term reduction in postoperative MIP prior to recovering to the preoperative state without significant difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Abreu et al 7 , quando comparadas a FMR e a função pulmonar pré-operatórias com os resultados do pós-operatório, foi encontrado que, na FMR, tanto a PImáx quanto a PEmáx apresentaram redução no pós--operatório. Santos et al 4 encontraram uma correlação negativa entre a PImáx e as CPPO.…”
Section: Discussionunclassified
“…Apesar de as cirurgias apresentarem altas taxas de cura, suas complicações como infecções, lesões de pele, deiscência de sutura, alterações musculoesqueléticas e vasculares, além de complicações cardíacas e pulmonares, estão presentes no pós-operatório 4 . Neste contexto, para um tratamento oncológico maximizado e bem-sucedido, é primordial uma cirurgia livre de complicações, ademais, identificar fatores de risco que predisponham a esse desfecho pode auxiliar na elaboração de estratégias de prevenção 5 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Among the possible postoperative complications, the main ones are: infection, skin lesions, injuries to the surgical incision, musculoskeletal and vascular alterations, and cardiac and pulmonary complications. In addition, there are some complications that can be caused due to the use of anesthesia to perform the procedure, among them are hypoventilation, immobility and impairment of the central nervous system (SANTOS, et al, 2020).…”
Section: Cancer Surgerymentioning
confidence: 99%